Science versus myths: the case of COVID-19 vaccine hesitancy - Friday Okonofua; Rose Ugiagbe (The Proceedings of the Nigerian Academy of Science, 2021)
The coronavirus disease 2019 (COVID-19), caused by a new strain of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) was first reported to the World Health Organization (WHO) from the first case in Wuhan, China on December 31, 2019. The WHO declared the disease a pandemic on March 10, 2020 due to the fast pace of its progression throughout the world. Given the high number of deaths and severe socio-economic consequences associated with the disease, and because of the limited uptake of public health measures designed to prevent the spread of the virus, it became evident that only the discovery of a vaccine would help prevent the community spread of the virus. In May 2020, the 73rd World Health Assembly issued a resolution recognizing the role of extensive immunization as a global public-health goal for preventing the transmission of SARS-COV-2 (WHO, 2020). Consequently, several scientific groups in various parts of the world began to work on developing vaccines against the virus. The first vaccines were introduced in September 2020, and since then the WHO has approved seven vaccines for use against COVID-19. These include 1) Biotech BBV152 COVAXIN vaccine, 2) Sinova-coronavac COVID-19 vaccine, 3) Pfizer BioNTech (BN T162 b2) COVID-19 vaccine, 4) Sinopharm COVID-19 vaccine, 5) Janssen Ad26.cov2.S COVID-19 vaccine, 6) the Oxford/AstraZeneca COVID-19 vaccine, and 7) the Moderna COVID-19 (mRNA-1273) vaccine.